The Worst or Average Availability: Option for the SLA Contract - Rados, I. (Elektronika ir Elektrotechnika, 2011)
This paper introduces a new term „the worst availability“. In the introductory part, the reasons why a high availability of the system is important are given as well as overviews of the former papers addressing the problem of the guaranteed availability in SLA contracts. Then, basic terms on availability are introduced with a special view on the parallel structure which can actually be applied to the ring network. The principles re protection of the wavelength channel which are used in the ring WDM networks are described separately. Furthermore the availability of the WDM ring which uses the protection of the wavelength channel is analysed, the expression for the worst availability of the WDM ring derived and the number of links of the working path which provide the worst availability determined. Data on the intensity of failures and mean time for the correction of certain components are taken from different literature. In the analysis, we suggested that it is about the WDM system with 64 wavelengths. At the end, the paper provides the answer to the question why in the SLA contracts, the worst availability needs to be requested and not average availability.